2018
DOI: 10.3389/fmicb.2018.02930
|View full text |Cite|
|
Sign up to set email alerts
|

A Nanostructured Lipid System to Improve the Oral Bioavailability of Ruthenium(II) Complexes for the Treatment of Infections Caused by Mycobacterium tuberculosis

Abstract: Tuberculosis (TB) is an infectious, airborne disease caused by the bacterium Mycobacterium tuberculosis that mainly affects the lungs. Fortunately, tuberculosis is a curable disease, and in recent years, death rates for this disease have decreased. However, the existence of antibiotic-resistant strains and the occurrence of co-infections with human immunodeficiency virus (HIV), have led to increased mortality in recent years. Another area of concern is that one-third of the world′s population is currently infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…This formulation demonstrated enhanced antimicrobial activity against M. tuberculosis [156]. For ruthenium complexes, incorporation into the NLC struc-ture resulted in increased bioavailability of ruthenium along with reduced toxicity [157].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…This formulation demonstrated enhanced antimicrobial activity against M. tuberculosis [156]. For ruthenium complexes, incorporation into the NLC struc-ture resulted in increased bioavailability of ruthenium along with reduced toxicity [157].…”
Section: Nanostructured Lipid Carriersmentioning
confidence: 99%
“…Likewise, Da Silva et al [ 303 ] investigated the antimycobacterial efficacy of Ru(II) heteroleptic compounds, known as SCARs. They found that these compounds maintain their efficacy when encapsulated in SLNs (labeled SCAR-SLN, composed of 10 % cholesterol, 10 % phosphatidylcholine, sodium oleate, and Eumulgin HRE 40, with 80 % of the formulation being phosphate buffer).…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…
Fig. 10 A) Temporal plasma concentration profile of Scar2-loaded NLS following a single oral administration via gavage at a dose of 300 mg/kg body weight, B) Intramacrophage activity of Scar-loaded nanosystems [ 303 ]. Reprint published from open access article by Frontiers Media S.A.
…”
Section: Nanoscale Drug Delivery Systemsmentioning
confidence: 99%
“…Colorimetric readings were performed on the spectrophotometer at 570 and 600 nm. Gentian violet (Synth, São Paulo, SP, Brazil) was used as the reference cytotoxic drug (Meira et al, 2017;Da Silva et al, 2018). EC 50 values were determined from data-points gathered from three independent experiments by using Graph Pad Prism version 5.01 (Graph Pad Software, San Diego, CA, United States).…”
Section: Cytotoxicity Evaluationmentioning
confidence: 99%